Peningkatan Efisiensi Kinerja Melalui Perancangan Website Surat Masuk di Dinas Pariwisata Kalimantan Timur - Siti Holipah; Sri Wahyuni; Ahmad Dzaky; Asslia Johar Latipah (BADAN PENERBIT STIEPARI PRESS, 2024)
This community service activity is motivated by the fact that the process of writing correspondence at the East Kalimantan Province Tourism Office still relies on manual techniques. Therefore, efforts are needed to provide education and improve technical skills related to designing a special website for management of entry letters at the Tourism Office. The main focus of this activity is to replace manual methods with more efficient information technology solutions, namely designing an incoming mail website. With this design, it is hoped that the Tourism Office can more easily manage and input correspondence, increase efficiency and reduce the potential for human error. The method used in developing this website is the prototype method, allowing the Tourism Department to directly participate in the design process and provide input to ensure that the final result meets their needs.